1994
DOI: 10.1021/j100074a025
|View full text |Cite
|
Sign up to set email alerts
|

An Atomically Resolved STM Study of the Interaction of Phosphine with the Silicon(001) Surface

Abstract: The interaction of phosphine (PH3) with the Si(OO1) surface has been investigated with scanning tunneling microscopy. At 300 K, PH3 adsorbs molecularly on top of a single Si=Si dimer with the phosphorus atom in a pentacoordinate configuration. Phosphine adsorption is accompanied by occasional ejection of silicon atoms from the substrate onto the surface, creating surfacevacancies and Si adatoms. Si atoms are preferentially ejected from defect sites. At high coverage, adsorbed PH3 molecules order into small reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
72
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 4 publications
15
72
1
Order By: Relevance
“…Some of the •-,7 eV reaction exothermicity is deposited in kinetic energy associated with motion parallel to the surface, and the product 0 atoms are found separated by tens of Angstroms. A similar situation was found by Hamers and coworkers for the dissociative chemisorption of Si 2 H 6 on Si(100) [29]. If these systems were studied at dilute coverages, so that reaction fragment pairs could be identified, the transient mobilities could be tabulated by measuring the separation of the fragment pairs.…”
Section: Application To Transient Surface Mobilitysupporting
confidence: 63%
“…Some of the •-,7 eV reaction exothermicity is deposited in kinetic energy associated with motion parallel to the surface, and the product 0 atoms are found separated by tens of Angstroms. A similar situation was found by Hamers and coworkers for the dissociative chemisorption of Si 2 H 6 on Si(100) [29]. If these systems were studied at dilute coverages, so that reaction fragment pairs could be identified, the transient mobilities could be tabulated by measuring the separation of the fragment pairs.…”
Section: Application To Transient Surface Mobilitysupporting
confidence: 63%
“…Yu et al [8] concluded from their experiments that around 675 0 C, all hydrogen atoms from PH 3 are desorbed and the surface is a monolayer (ML) P covered Si(001) with the formation of P-P dimers. Wang et al [9] did a scanning tunneling microscopy (STM) and Auger electron spectroscopy (AES) study of phosphorous-terminated Si(001) surface close to a monolayer P coverage. They find mostly P-P dimers, along with some Si-P dimers on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…These reaction products include H, SiH 2 and SiH 3 [38,39]. For example bright spots in images at bridge-bonded positions are inferred to be SiH 2 , whereas adsorbates appearing at dangling bond sites are attributed to SiH 3 [39]. These assignments are corroborated by observing the reaction of these species, such as metastable adsorbed SiH 3 apparently fragmenting into adsorbed SiH 2 and H. Nonetheless, there remain disagreements as to some of these assignments.…”
Section: Contrast In Stm Imagingmentioning
confidence: 90%
“…Recent progress on semiconductor surfaces has been made by Boland and by Hamers and coworkers who have used a combination of STM imaging, spectroscopy and adsorption site coordination in order to identify hydrogen at various sites and reacted disilane fragments on the Si(100) surface [38,39]. These reaction products include H, SiH 2 and SiH 3 [38,39].…”
Section: Contrast In Stm Imagingmentioning
confidence: 99%
See 1 more Smart Citation